Modulation of tau isoforms by RNA reprogramming: Functional consequences and therapeutic perspectives - Avale, Maria Elena (2019)
Tauopathies are neurodegenerative diseases characterized by the presence of intraneuronal aggregates of the protein tau in insoluble neurofibrillary tangles (NFTs). Tau is a microtubule-associated protein predominantly expressed in neurons, which participates in microtubule polymerization and axonal transport. Alternative splicing of exon 10 (E10) in the Tau transcript produces protein isoforms with three (3R) or four (4R) microtubule binding repeats, which are expressed in equal amounts in the normal adult human brain. Several tauopathies are associated with mutations affecting exon 10 alternative splicing, leading to an imbalance between 3R and 4R isoforms. Correction of that imbalance represent a potential therapeutical approach for those tauopathies.Here we present our achievements using a trans-splicing RNA reprogramming strategy to modulate the 3R:4R tau ratio, either in cultured post-mitotic human neurons differentiated in vitro or into the mouse brain. Lentiviral vectors were used to express molecules that modulate E10 inclusion/exclusion by RNA trans-splicing with the endogenous tau transcript. Tau isoforms were quantified by qPCR and western blot. Morphological analyses and live imaging axonal transport indicate that perturbations in the tau 3R:4R ratio in human neurons impaired axonal transport dynamics without altering neuronal morphology. In a mouse model of tauopathy (htau mice) local modulation of E10 inclusion in the prefrontal cortex improved cognitive deficit, restored neuronal firing patterns and reduced insoluble and hyperphosphorylated tau contents. Moreover, local shifting of 3R to 4R tau in the striatum improved motor coordination deficits in htau mice.Together, our results evidence some of the (dys)functional consequences of tau 3R:4R imbalance and rise the potential use of RNA reprogramming to correct tau mis-splicing in human tauopathies.